Comorbidity between epilepsy and autism from the point of view of ontogenesis - G. V. Kuzmich; A. N. Sinelnikova (Русский журнал детской неврологии)
Early childhood autism, or autism spectrum disorders, is an extremely heterogeneous group of conditions that share similar symptoms  of dysontogenesis. Epilepsy is the most significant comorbidity in autism. The present article covers various aspects of comorbidity between epilepsy and autism, described in the literature over the last 50 years. This review aims to analyze the development of epilepsy and autism during ontogenesis and to identify causal relationships between these diseases, considering the information on the two age peaks for epilepsy onset in patients with autism.